Diversity of anammox bacteria and contribution to the nitrogen loss in surface sediment. (August 2019) - Wu, Jiapeng; Hong, Yiguo; Ye, Jiaqi; Li, Yiben; Liu, Xiaohan; Jiao, Lijing; Li, Tongxin; Li, Yuwei; Bin, Liying; Wang, Yu
Abstract: Anaerobic ammonium oxidizing bacteria are the key players of nitrogen cycling in different kinds of ecosystems. Here, the abundance, activity, and community composition of anammox bacteria in the surface sediments of Jiaozhou Bay (JZB) were investigated. Results indicated that dominant OTUs with 97% similarity were affiliated to Ca. Scalindua (75.37%), Ca. Brocadia (9.40%), Ca. Kuenenia (1.46%), Cluster 1 (5.41%), and Cluster 2 (8.36%) by high-throughput sequencing analysis. The abundance of anammox bacteria were quantified by anammox specific 16S rRNA gene, which ranged from (5.88 ± 1.20) × 10 4 to (1.41 ± 0.08) × 10 6 copies per gram. Anammox rates in JZB, measured by 15 N tracing technique, ranged from 0.01 to 0.24 nmol N g −1 h −1, contributing 0.07%–18.55% to N2 production, and the sediment nitrogen loss caused by anammox was estimated at 1042.33 t N per year. NH4 + and NO2 − contents were the limiting factors affecting the anammox bacterial community composition and abundance, respectively. Meanwhile, high NO3 − favors the growth of diverse anammox bacteria in surface sediments of JZB. Overall, these results significantly enhance our understanding of the anammox activity, community composition, and nitrogen removal contribution in hypernutrified and semi-closed bay. Highlights: Diverse anammox bacteria were detected in surface sediments of JZB. Anammox rates ranged from 0.01 to 0.24 nmol N g −1 h −1, contributing 0.07-18.55% to N2 production. High NO3 − favors the growth of diverse anammox bacteria in surface sediments of JZB. The N loss by anammox was estimated to reach 1042.33 t N year −1 in surface sediments of JZB.